Association of Marital Quality, Loneliness and Demographic Variables among Healthcare Professionals: A Cross-sectional Study from Gujarat, India - Kanishka Varyani; Ritu Sharma (Journal of Clinical and Diagnostic Research)
Introduction: Marital quality, generally understood as a global evaluation of marriage based on certain criteria, is a significant determinant of psychological wellbeing and work efficacy among individuals, particularly among Healthcare Professionals (HCPs) facing high-stress environments and long working hours. Recently, the World Health Organisation (WHO) has recognised loneliness as a global threat with serious negative impacts on physical and mental health, affecting diverse populations, including HCPs. Aim: To investigate marital quality among HCPs and its association with loneliness, as well as demographic variables such as age, gender and duration of marriage. Materials and Methods: This cross-sectional research was conducted from September 2023 to January 2024, including 199 married HCPs practicing as doctors, nurses, or administrative staff in hospitals or clinics in Gujarat, India, based on their marital status and voluntary participation in the study. A semistructured questionnaire was used for demographic details, along with the Marital Quality Scale (MQS) and University of California Los Angeles (UCLA) Loneliness Scale (version 3) to collect data. Cross-tabulation, Chi-square (χ2) and Pearson correlation were used to analyse the data in Statistical Package for the Social Sciences (SPSS) software version 28.0. Results: Out of the 199 participants, 120 were males (60.30%) and 79 were females (39.70%). The average age of the participants was 42.8±9.12 years. An overwhelming majority of 152 HCPs (76.4%) reported severely impacted marital quality. A strong and significant correlation was observed between marital quality and loneliness (r=0.609, p-value<0.001). A non significant correlation was observed between age and marital quality (r=0.061, p-value=0.396) and loneliness (r=-0.048, p-value=0.505). Similar results were also observed between the duration of marriage and marital quality (r=0.033, p-value=0.644) and loneliness (r=-0.023, p-value=0.747). Conclusion: The findings suggest that interventions to enhance marital quality among HCPs should focus more on interpersonal and situational factors such as communication style, conflict resolution, support from the spouse, increasing empathy, sexual satisfaction and intimacy, rather than demographic variables.